FACTORS RELATED TO ANXIETY LEVEL IN ELDERLY RETIREMENTS IN SEROJA PUSKESMAS, BEKASI CITY 2022 - Hanna Rada Soraya; Riris Ocktryna Silitonga; Nurti Y. K. Gea (Rena Cipta Mandiri, 2024)
Background: Aging is a process of slowly disappearing – gradually the ability of tissues to repair themselves or maintain their normal function so that they cannot survive the infection and repair the damage suffered. Anxiety the appearance of a fear or worry in something unclear and related to feelings of uncertainty and helplessness Factors causinganxiety in the elderly . Internal factors (biological, psychological, socio-cultural) : external factors (gender, age, social support, economic status). Researcher's Objective:Knowing the factors related to the level of anxiety in the retired elderly at the Seroja Kota Bekasi Health Center 2022. Research Method: The design in this study used Observational Analytics with a Cross Sectional research design, using independent variables of factors causing elderly packaging and a type of random sampling with a total sample of 88 respondents. The instruments in this research used digital questionnaires and interviews and were conducted using Chi Square. Researcher results:Based on statistical analysis with a significance level of 95% or a α value (0.05) chi square test results obtained p value (0.562) > α value (0.05) the results did not have a significant relationship between sex and anxiety level in respondents this showed Ha was rejected, 95% significance level or α value (0.05) Chi Square test results obtained p value (0.134) > α value (0.05) so that it can be concluded from these results there is no significant relationship between age and anxiety level in respondents this shows Ha is rejected, a significance level of 95% or a α value (0.05) chi square test results obtained p value (0.000) < α value (0.05) so that it can be concluded from these results there is a relationship between economic status and anxiety level in respondents this shows H0 is rejected, with a significance level of 95% or a value of α (0.05) chi square test results obtained p value (0.000) < value α (0.05) so that it can be concluded from these results there is a relationship between family support and the level of anxiety in respondents this shows that H0 is rejected. Thus it can be interpreted that